Bismarck; The Story of a Fighter - Ludwig, Emil; Translated by Paul, Eden; Paul, Cedar (London George Allen & Unwin Ltd., 1927)
Previously published: Boston: Little, Brown and company, 1927; originally published in German as: Bismarck: geschichte eines k'ampfers. Berlin: E. Rowohlt, 1926.
Include Illustrations, Chronology and Index.
English Biography.
Keywords: Bismarck, Otto, Fürst von, 1815-1898 -- Statesmen -- Germany